Effect of a Proposed Unit on Color Idioms on Developing Cultural Awareness and Attitudes toward Translation among Non-specialist Students of English - ماجد محمدين (Faculty of Education - Port Said University, 2021)
Language is a tool of communication between cultures. Color idioms are language expressions that are used beyond their apparent meanings, using colors to express moods and feelings. They are culture bound and is only fully understood through understanding of their original culture. The aim of this study was to propose an instructional unit on color idioms, and investigate its effectiveness on the development of cultural awareness skills and attitudes toward translation among non-specialist students of English at Port Said Faculty of Education. It was an experimental study of one-group design, conducted in the first semester of the academic year 2020/2021. Data were collected from (22) participants through two scales: a scale on participants' cultural awareness skills and another scale on their attitudes toward translation, both prepared by the researcher. Later, sets of data were statistically analyzed using different statistical techniques. The results of the analyses revealed that participants had developed their cultural awareness skills and maintain better attitudes toward translation. In the light of findings, necessary implications, suggestions for further research, and recommendations were provided for curricula and policy makers, researchers, teachers, and students regarding raising cultural awareness and developing positive attitudes towards translation.